Expression of the gene encoding the matrix gla protein by mature osteoblasts in human fracture non-unions. Issue 2 (1st April 1999) - Lawton, D M; Andrew, J G; Marsh, D R; Hoyland, J A; Freemont, A J
Abstract : BACKGROUND: Osteoblast phenotypic abnormality, namely the expression of collagen type III, has been shown previously in fracture non-union woven bone. AIMS: To investigate osteoblasts from fracture non-unions for evidence of gene expression of non-collagenous bone matrix proteins that have been implicated in mineralisation, namely matrix gla protein (MGP), osteonectin, osteopontin, and osteocalcin. MGP is a consistent component of bone matrix, but there are no reports of osteoblasts in the skeleton expressing the gene for MGP, and the site of synthesis of skeletal MGP (perhaps the liver) has yet to be determined. METHODS: Biopsies from normally healing human fractures and non-unions were examined by means of in situ hybridisation, using 35S labelled probes and autoradiography to disclose levels of gene expression. RESULTS: In normally healing fractures, mature osteoblasts on woven bone were negative for MGP mRNA, but positive for osteonectin, osteopontin, and osteocalcin mRNA molecules. In non-unions, osteoblasts displayed a novel phenotype: they were positive for MGP mRNA, in addition to osteonectin, osteopontin, and osteocalcin mRNA molecules. CONCLUSIONS: Mature osteoblasts in slowly healing fractures have an unusual phenotype: they express the gene encoding MGP, which indicates that control of osteoblast gene expression in non-unions is likely to be abnormal. This might be of importance in the pathogenesis of non-uniting human fractures, and is of current interest given the emerging status of MGP as an inhibitor of mineralisation.